2006
DOI: 10.1177/0002764206289140
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Money

Abstract: A sociocultural understanding of affordability is essential to understanding the college cost deliberations of low-income African American and Latino students and their families. Habitus shapes and informs college affordability decisions for students and their families. Using interviews with 63 college counselors in urban secondary schools, low-income underrepresented students’ assessments of affordability were framed by a highly individualized assessment of need, an internalized calculation of costs versus be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…Thus, in our model, college socialization is measured by whether or not students have met with high school counselors regarding college admission, as well as participating in college preparatory programs that are designed to inform and assist student access and choice. Research has found that college counselors influence the college trajectories of Latinx students, as they are a primary source of college admissions and financial aid information [25][26][27][28]. Meeting with college counselors can have positive effects like increasing the number of applications that Latinx students submit [27].…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, in our model, college socialization is measured by whether or not students have met with high school counselors regarding college admission, as well as participating in college preparatory programs that are designed to inform and assist student access and choice. Research has found that college counselors influence the college trajectories of Latinx students, as they are a primary source of college admissions and financial aid information [25][26][27][28]. Meeting with college counselors can have positive effects like increasing the number of applications that Latinx students submit [27].…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Meeting with college counselors can have positive effects like increasing the number of applications that Latinx students submit [27]. However, research has also found that many low-income Latinx students attend high schools that lack counselor resources or have high student to counselor ratios, at times exceeding 1000 students to 1 counselor [26,29]. High school counselors have been found to have lower expectations of low-income Latinx students, which results in biased information relayed to the student about their college prospects [26].…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations